Characteristics of Intraoperative Hemodynamic Instability in Postoperatively Diagnosed Pheochromocytoma and Sympathetic Paraganglioma Patients - Kim, Jung Hee; Lee, Hyung-Chul; Kim, Su-jin; Lee, Kyu Eun; Jung, Kyeong Cheon (Frontiers in Endocrinology, 2022)
Background: Despite an improved understanding of pheochromocytoma and extra-adrenal sympathetic parganglioma (PPGL), including diagnosis and management, some PPGLs are postoperatively diagnosed. Clinical characteristics and intraoperative haemodynamic instability (HI) in postoperatively diagnosed PPGL patients have been poorly defined. Thus, we investigated the clinical characteristics and HI in patients with postoperatively diagnosed PPGLs compared to patients with preoperatively diagnosed PPGLs. Methods: We obtained clinical and haemodynamic data from the electronic medical records of 256 patients with pathologically confirmed PPGLs at our institution from January 2005 to December 2019. We assessed the intraoperative HI (systolic blood pressure [SBP]>160 mmHg (min) or mean blood pressure [MBP]<60 mmHg (min)) over time. Results: Twenty-nine patients (11.3%) were diagnosed with PPGLs postoperatively. Hypertension (34.5% vs. 63.0%, P=0.006) and pheochromocytoma (17.2% vs. 81.1%, P<0.001) case rates were lower in postoperatively diagnosed patients than in preoperatively diagnosed patients. Preoperative SBP in the ward was similar between groups, but the use of α-blockers and β-blockers was more frequent in preoperatively diagnosed patients (89.0% vs. 3.4%, P<0.001; 36.3% vs. 6.9%, P=0.003). Considering intraoperative HI, postoperatively diagnosed patients demonstrated a similar percentage of time with SBP>160 mmHg (median [IQR]; 7.9% [2.5; 11.9] % vs. 4.6% [0.0; 11.9], P=0.088) but a significantly lower percentage of time with MBP<60 mmHg (0.0% [0.0; 3.0] vs. 5.6% [0.0, 12.6], P=0.002) compared with preoperatively diagnosed patients. Conclusions: Patients diagnosed with PPGLs postoperatively may have no further higher risk of intraoperative hypertension than those diagnosed preoperatively. This may suggest that intrinsic tumour characteristics of PPGLs and intraoperative management are more crucial for avoiding haemodynamic stability than universal preoperative use of α- and β-blockers in postoperatively diagnosed PPGL patients.